Troubled Financing Rescue Strategy in Musyarakah Financing: PT. Sharia NTB Bank - Riduan Mas’ud (UIN Sunan Gunung Djati, 2022)
This study aims to evaluate the strategy undertaken by PT. Bank NTB Syariah in dealing with problems in musyarakah financing both in terms of policy and law. This research is descriptive qualitative research. The data in this study were obtained through an interview process with leaders from PT. Bank NTB Syariah and the analyst section of Bank NTB Syariah. Based on the results obtained, it can be concluded that PT. Bank NTB Syariah faces several problems, including weak supervision, availability of human resources, untrustworthy customers, customers who retire early, unstable weather, stalled project terms, customer death, not optimal Collateral, covid-19, to natural disasters. Steps that need to be taken by PT. Bank NTB Syariah is restructuring all aspects of financing. In addition, transaction systematics needs to be improved periodically